FACTORS ASSOCIATED WITH DEPRESSION AMONG CHRONIC KIDNEY DISEASE PATIENTS RECEIVING HEMODIALYSIS - Isdiana, Dini Fitria; Mugi Hartoyo; Umi Margi Rahayu; Rodhi Hartono; Budiyati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Chronic  kidney  disease  (CKD)  is  one  of  the  therapies  for  CKD  is hemodialysis. Hemodialysis can have psychological effects, one of which is depression. The purpose of this study was to identify factors associated with depression in patients with chronic kidney failure undergoing hemodialysis. This  is  a  quantitative  study  with  a  descriptive  correlational  design  using  a cross-sectional design on 52 samples with purposive sampling. The study was conducted  using  the  Beck  Depression  Inventory  II  questionnaire,  Fatigue Severity  Scale,  Pittsburgh  Sleep  Quality  Index,  and  data  were  tested  using Kendall's Tau b and c tests and Ordinal Logistic Regression. The study found that 46.2% of CKD patients experienced severe depression. Depression was more  prevalent  among  CKD  patients  aged  41–55  years  (40.0%),  females (61.5%),  married  individuals  (65.4%),  those  with  a  high  school  education (40.4%), those who had undergone hemodialysis for 13–36 months (44.2%), respondents  with  poor  sleep  patterns  (55.8%),  and  those  with  comorbid conditions  (hypertension)  (34.6%).  The  results  of  Kendall's  tau  analysis showed that factors associated with depression include age, gender (p=0.001), marital  status  (p=0.001),  duration  of  hemodialysis  (p=0.016),  education (p=0.001),  sleep  patterns  (p=0.001),  fatigue  (p=0.001),  and  comorbidities (p=0.001), while age did not show a significant association (p=0.057). Among the  factors  analyzed  using  the  partial  test,  no  single  factor  was  dominant  in influencing  depression  levels  in  CKD  HD  patients.  The  odds  ratio  for education was the highest, with a value of 603,801.0287. Clinically, the odds ratio  results  indicate  that  education  is  the  dominant  factor,  with  a  60-fold influence on depression in CKD HD patients.